Physiological changes in Chlamydomonas reinhardtii after 1000 generations of selection of cadmium exposure at environmentally relevant concentrations. Issue 6 (4th May 2018) - Yu, Zhen; Wei, Huiling; Hao, Rui; Chu, Huashuo; Zhu, Yi
Abstract : Chlamydomonas reinhardtii failed to evolve specific adaptation to high cadmium concentrations after 1000 generations of selection of cadmium exposure at environmentally relevant concentrations. Abstract : Cadmium (Cd) is a nonessential and toxic trace element widely existing in waters through various anthropogenic activities such as mining and waste disposal. The physiological responses of aquatic organisms to long-term Cd exposure at environmentally relevant concentrations are still not well explored. In the present study, two strains of unicellular green algae Chlamydomonas reinhardtii, a walled strain CC125 and a wall-less strain CC406 were selected to investigate the physiological changes of aquatic organisms after long-term Cd exposure at environmentally relevant concentrations (4.92 and 49.2 μg L −1 ). After about 1000 generations of selection, all of the two strains showed higher intracellular lipid peroxidation and lower photosynthetic activities, and failed to evolve specific adaptation to high levels of Cd (4.92 mg L −1 ) compared to the control. However, short-term low dose Cd exposure exerted hormetic effects on C. reinhardtii and the hormetic stimulation of growth rate, chlorophyll contents and photochemical activities at the lower concentration of Cd (4.92 μg L −1 ) groups were more pronounced than those at higher ones (49.2 μg L −1 ). Taken together, this study confirmed that long-term exposure to Cd at environmentally relevant concentrations which were regarded as nontoxic in acute experiments would produce toxic effects on C. reinhardtii and should be paid more attention.